2018
DOI: 10.1111/jocd.12440
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between the efficacy of microneedling combined with 5‐fluorouracil vs microneedling with tacrolimus in the treatment of vitiligo

Abstract: Microneedling combined with 5-fluorouracil or tacrolimus is safe and effective treatment of vitiligo. However, 5-fluorouracil achieved a greater percentage of repigmentation than tacrolimus particularly in the acral parts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
82
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(102 citation statements)
references
References 21 publications
(52 reference statements)
7
82
3
Order By: Relevance
“…12 In our study, flat, non-resistant hairy areas showed more repigmentation (mean 13.8±8.5%) as compared to non-flat, resistant, non-hairy areas (mean 9.8±4.5%). This is contrary to Mina et al, 13 who reported that 40% of acral vitiliginous patches showed good to excellent repigmentation mainly diffuse but the pattern was perifollicular as shown in our study.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…12 In our study, flat, non-resistant hairy areas showed more repigmentation (mean 13.8±8.5%) as compared to non-flat, resistant, non-hairy areas (mean 9.8±4.5%). This is contrary to Mina et al, 13 who reported that 40% of acral vitiliginous patches showed good to excellent repigmentation mainly diffuse but the pattern was perifollicular as shown in our study.…”
Section: Discussioncontrasting
confidence: 99%
“…In the study by Anbar et al, 4 the authors reported pain in all their patients, and a higher prevalence of hyperpigmentation in 30%. Interestingly in the study using microneedling with 5-FU, 13 although they reported the procedure to be well tolerated, patients developed hyperpigmentation in 16%, inflammation in 12%, and ulceration in 4% of patients, all more severe side effects than what is reported in our study.…”
Section: Discussioncontrasting
confidence: 68%
“…Microneedling combined with drugs was found to be safe and effective treatment of vitiligo. However, in the case of 5‐fluorouracil a greater percentage of repigmentation was achieved in comparison to tacrolimus (Mina, Elgarhy, Al‐Saeid, & Ibrahim, ).…”
Section: Main Indications For the Application Of Microneedlingmentioning
confidence: 99%
“…Microneedling combined with drugs was found to be safe and effective treatment of vitiligo. However, in the case of 5-fluorouracil a greater percentage of repigmentation was achieved in comparison to tacrolimus (Mina, Elgarhy, Al-Saeid, & Ibrahim, 2018). Korobko I et al performed a pilot comparative study of topical latanoprost and tacrolimus in combination with narrow-band ultraviolet B phototherapy and microneedling for the treatment of nonsegmental vitiligo.…”
Section: Vitiligomentioning
confidence: 99%
“…Moreover, a possible mechanical migration of melanocytes from the pigmented borders to the depigmented areas has been postulated. [ 89‐91 ] The wounding action of chemical peels has been reported in patients with vitiligo. Treatment with 88% phenol peeling in stable vitiligo lesions produced a repigmentation of 82.5% of hairy sites and 81.3% of non‐hairy .…”
Section: Proposed Treatmentsmentioning
confidence: 99%